Communicating palliative hope in late-stage dementia: Thematic analysis of hope work in care plan meetings with nursing home residents’ families - Paananen, Jenny; Logren, Aija (Oxford University Press (OUP), 2026)
Objectives
The study analyzes how nursing home professionals communicate palliative hope in care plan meetings with family members of residents with late-stage dementia.
Methods
Eleven care plan meetings between nursing home professionals and residents’ family members at Finnish nursing homes were video- or audio-recorded and analyzed with inductive thematic analysis. Data were collected in 2020–2021 using convenience sampling: All nursing homes within one region in Finland were contacted with the help of the local Memory Association, and all volunteers were accepted as study participants.
Results
We identified three main themes of palliative hope in late-stage dementia: 1) Life is good and there is still time, 2) Agency and identity are not lost, and 3) Death will be good and professional support is available.
Discussion
As overarching goals of hope work, we identified acceptance and appreciation. Nursing home professionals have an important role in constructing and maintaining hope and thus supporting families. They can remind families that residents are not lost as people, they are in good care, and that there are still time and opportunities for a good life, meaningful moments, and connection, which families can appreciate despite the progressive illness. By highlighting the possibility of a peaceful death for the resident and willingness to support families in the end-of-life phase, nursing home professionals can help families accept the inevitable. Combined with good-quality palliative care, palliative hope work can support families’ social relationships and foster meaningful experiences at the end-of-life stage.